2019
DOI: 10.1021/acssynbio.9b00106
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial MbtH-like Proteins Stimulate Nonribosomal Peptide Synthetase-Derived Secondary Metabolism in Filamentous Fungi

Abstract: Filamentous fungi are known producers of bioactive natural products, low molecular weight molecules that arise from secondary metabolism. MbtH-like proteins (MLPs) are small (∼10 kDa) proteins, which associate noncovalently with adenylation domains of some bacterial nonribosomal peptide synthetases (NRPS). MLPs promote the folding, stability, and activity of NRPS enzymes. MLPs are highly conserved among a wide range of bacteria; however, they are absent from all fungal species sequenced to date. We analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…MLPs have been studied extensively in recent years, and yet the exact function remains still unknown. Growing evidence suggests that they can increase the activity of A domains as well as enhance the soluble expression of their partner NRPSs (Boll et al., 2011 ; Felnagle et al., 2010 ; Zwahlen et al., 2019 ), although in some cases the deletion of the MLP gene from a cluster does not have any effect on the biosynthesis of the NRP (Stegmann et al., 2006 ). An interesting feature of MLPs is that they can activate non-cognate NRPSs as well, both in vivo and in vitro (Boll et al., 2011 ; Lautru et al., 2007 ; Wolpert et al., 2007 ; Zhang et al., 2010 ; Zwahlen et al., 2019 ).…”
Section: Interactions With Helper Proteins and Other Associated Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…MLPs have been studied extensively in recent years, and yet the exact function remains still unknown. Growing evidence suggests that they can increase the activity of A domains as well as enhance the soluble expression of their partner NRPSs (Boll et al., 2011 ; Felnagle et al., 2010 ; Zwahlen et al., 2019 ), although in some cases the deletion of the MLP gene from a cluster does not have any effect on the biosynthesis of the NRP (Stegmann et al., 2006 ). An interesting feature of MLPs is that they can activate non-cognate NRPSs as well, both in vivo and in vitro (Boll et al., 2011 ; Lautru et al., 2007 ; Wolpert et al., 2007 ; Zhang et al., 2010 ; Zwahlen et al., 2019 ).…”
Section: Interactions With Helper Proteins and Other Associated Enzymesmentioning
confidence: 99%
“…Growing evidence suggests that they can increase the activity of A domains as well as enhance the soluble expression of their partner NRPSs (Boll et al., 2011 ; Felnagle et al., 2010 ; Zwahlen et al., 2019 ), although in some cases the deletion of the MLP gene from a cluster does not have any effect on the biosynthesis of the NRP (Stegmann et al., 2006 ). An interesting feature of MLPs is that they can activate non-cognate NRPSs as well, both in vivo and in vitro (Boll et al., 2011 ; Lautru et al., 2007 ; Wolpert et al., 2007 ; Zhang et al., 2010 ; Zwahlen et al., 2019 ). In the most recent of these works, it has been shown that the heterologous expression of bacterial MLPs can boost the production of NRPS-related secondary metabolites in the filamentous fungus Penicillium chrysogenum (Zwahlen et al., 2019 ).…”
Section: Interactions With Helper Proteins and Other Associated Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although STRING is not specifically targeted towards metagenomics or natural product biosynthesis, it can be used to predict–protein interactions such as for MbtH-like proteins in NRPS systems. 147 A more specific tool, CO-ED, is useful for network analysis and identification of unusual co-occurring domains in multi-domain proteins including megasynthases commonly involved in natural product biosynthesis. 148 CO-ED relies on PFAM information as inputs which can be extracted from (meta)genomes using PfamScan.…”
Section: On the Road: Computational Methods For Enzyme Function Predictionmentioning
confidence: 99%
“…CloY from the clorobiocin BGC of S. roseochromogenes (Table 3; Pojer et al, 2002) is essential for production of the aminocoumarin antibiotic (Wolpert et al, 2007), as it is required for the solubility and adenylation activity of its corresponding NRPS partner, CloH (Boll et al, 2011). The ComB-encoding gene is situated within a glycopeptide-like complestatin NRP BGC from S. lavendulae (Chiu et al, 2001) and was recently shown to stimulate the production of several NRPs in the mold Penicillium chrysogenum, which does not harbor any MLP-encoding genes in its genome (Zwahlen et al, 2019). YbdZ has been extensively investigated in recent studies and is required for the biosynthesis of the ENT siderophore in E. coli (Schomer and Thomas, 2017;Schomer et al, 2018).…”
Section: Selection Of Non-cognate Mlps For Functional Studiesmentioning
confidence: 99%